Early postoperative decrease of albumin is an independent predictor of major complications after oncological esophagectomy: A multicenter study. Issue 2 (1st December 2020) - Labgaa, Ismail; Mantziari, Styliani; Genety, Maxime; Elliott, Jessie A.; Kamiya, Satoshi; Kalff, Marianne C.; Winiker, Michaël; Pasquier, Jérôme; Allemann, Pierre; Messier, Marguerite; van Berge Henegouwen, Mark I.; Nilsson, Magnus; et al.
Abstract: Background and Objectives: Serum albumin perioperative decrease (∆Alb) may reflect the magnitude of the physiological stress induced by surgery. Studies highlighted its value to predict adverse postoperative outcomes, but data in esophageal surgery are scant. This study aimed to investigate the role of ∆Alb to predict major complications after esophagectomy for cancer. Methods: Multicenter retrospective study conducted in five high‐volume centers, including consecutive patients undergoing an esophagectomy for cancer between 2006 and 2017. Patients were randomly assigned to a training ( n  = 696) and a validation ( n  = 350) cohort. Albumin decrease was calculated on postoperative day 1 and defined as ΔAlb. The primary endpoint was major complications according to Clavien classification. Results: In the training cohort, esophagectomy induced a rapid drop of albumin. Cut‐off of ΔAlb was established at 11 g/L and allowed to distinguish patients with adverse outcomes. On multivariable analysis, ΔAlb was identified as an independent predictor of major complications (OR, 1.06; 95% CI, 1.01–1.11; p  = .014). Higher BMI and laparoscopy were associated with lower ΔAlb. Analysis of the validation cohort provided consistent findings. Conclusions: ΔAlb appeared as a promising biomarker after oncological esophagectomy, allowing prediction of potential adverse outcomes.